Diffuse pulmonary haemorrhage accompanied by haemothorax as a rare presentation of primary lung angiosarcoma - Modrzewska, Katarzyna; Radzikowska, Elżbieta; Szołkowska, Małgorzata; Oniszh, Karina; Szczęsna, Magdalena; Roszkowski-Śliż, Kazimierz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Primary pulmonary angiosarcoma is an extremely rare disease. Chest computed tomography demonstrates solitary or multifocal lesions, sometimes associated with ground-glass opacities or pleural effusion. Diagnosis is based on histological examination that reveals spindle-shaped epithelioid cells with positive staining for endothelial markers (factor VIII, CD 31, CD34, Fli-1, Ulex europaeus agglutinin 1, vimentin). The prognosis is poor and effective treatment is still being researched. This is a report of a 65-year-old patient with a four-month history of haemoptysis, cough, and dyspnoea. The primary radiological findings suggested interstitial lung disease. After one month the clinical presentation evolved into diffuse pulmonary haemorrhage with concomitant haemothorax. The diagnosis of primary lung angiosarcoma was based on histological and immunohistochemical examination of the lung and pleural biopsy